Avaliação da atividade antioxidante de cogumelo do sol (Agaricus blazei Murril) e sua aplicação em linguiça - Stefanello, Flávia Santi (2013)
This study aimed to verify the antioxidant activity of sun mushroom (Agaricus blazei Murrill) and its antioxidant effect in pork sausage. First drawn up the hydroethanolic extracts with different extraction times and temperatures, making the characterization of the total phenolics composition and antioxidant activity in vitro. After the extracts obtained at 70 ° C for 60 minutes at concentrations of 0%, 0.5%, 1.0% and 2.0% and also the sun mushroom powder, at concentrations of 0% , 1.0%, 2.0% and 4.0% were applied to pork sausage. Moisture, protein, ash and fat was analysed to characterize the products and every seven days was performed the analyzes of pH, color, TBARS values and microbiological counts. Sensory analysis was assessed by testing the acceptability through a hedonic scale with seven points and the purchase intent test. The results on the chemical composition, as well as the microbiological analysis for coagulase positive Staphylococcus, Coliforms at 35 º C and 45 º C, Salmonella and Clostridium sp sulfite reducer were in compliance with Brazilian legislation. With respect to product color, those treatments added sun mushrooms, both in extract form as powder, exhibited a yellowish color. At the end of the storage (21 days), the amount of TBARS for the sausages added with 2.0% of the sun mushroom extract was 0.705 ± 0.01 mg MDA/kg of sample and control 1.097 ± 0.11 mg MDA/kg of sample, while the 35th day, the amount of TBARS for sausages added with 1.0%, 2.0% and 4.0% sun mushroom powder was 0.604 ± 0.12 , 0.585 ± 0.11, 0.509 ± 0.12 mg MDA/Kg of sample, respectively, and control 1.131 ± 0.12 mg MDA/Kg of sample. The sun mushroom has no effect on the microbiological stability during storage, as assessed by counting the total mesophilic aerobic and psychrotrophic microorganisms. Regarding sensory characteristics showed good acceptability by consumers. Thus, it is concluded that the hydroethanolic extract of sun mushroom (Agaricus blazei Murrill) proved to be effective on the oxidative stability of pork sausage when added in a concentration of 2.0% by extending the shelf life up to 21 days storage, while in powder form was shown to be effective when added at a concentration of 1.0%, 2.0% and 4.0%, extending the shelf life up to 35 days under conditions of packaging permeable to oxygen and temperature cooling (+ 4 ° C) with a viable applicability as a natural antioxidant source with better performance in powder form.